"Wriggling rotters" in the oral cavity: A rare case report - Roopashri Govindaraju; Vaishali Mysore Rajshekar; Maria Priscilla David; Sangeetha Shivraj (Wolters Kluwer Medknow Publications, 2014)
Myiasis is derived from a Latin word "Muia," which means fly and "iasis," which means disease. It is a pathological condition in which there is an infestation of living mammals with the dipterous larvae, which, at least for a certain period feed on the host's dead or living tissue and develop as parasites. Oral myiasis is a rare pathology in humans and is associated with poor oral hygiene, alcoholism, senility, suppurating lesions, severe halitosis, malignancy, low socioeconomic status and others conditions. The treatment consists of mechanical removal of the maggot one by one along with a systemic treatment of ivermectin, a semi-synthetic macrolide antibiotic. We present a case report of a 25-year-old man with intellectual disability, poor oral hygiene, epilepsy, with a deep lacerated wound in the gingiva of maxillary anterior region with acute swelling of the upper lip and presence of larvae of maggot.